Functionality of major histocompatibility complex class II molecules in mice doubly deficient for invariant chain and H-2M complexes - Tourne, Sylvie (The National Academy of Sciences of the USA, 1997)
By combining two previously generated null mutations, Ii° and M°, we produced mice lacking the invariant chain and H-2M complexes, both required for normal cell-surface expression of major histocompatibility complex class II molecules loaded with the usual diverse array of peptides. As expected, the maturation and transport of class II molecules, their expression at the cell surface, and their capacity to present antigens were quite similar for cells from Ii°M° double-mutant mice and from animals carrying just the Ii° mutation. More surprising were certain features of the CD4(+) T cell repertoire selected in Ii°M° mice: many fewer cells were selected than in Ii(+)M° animals, and these had been purged of self-reactive specificities, unlike their counterparts in Ii(+)M° animals. These findings suggest (i) that the peptides carried by class II molecules on stromal cells lacking H-2M complexes may almost all derive from invariant chain and (ii) that H-2M complexes edit the peptide array displayed on thymic stromal cells in the absence of invariant chain, showing that it can edit, in vivo, peptides other than CLIP.